Ex-ante heterogeneity, separations, and labor market dynamics - César Barreto; Christian Merkl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2024)
Our paper documents the importance of workers' ex-ante heterogeneity for labor market dynamics and for the composition of the unemployment pool. We show that workers with high wages have both lower separation rates and larger log-deviations of these separations over the business cycle than those with low wages. Thereby, more high-wage workers enter the unemployment pool in recessions, leading to a positive correlation between unemployment and the prior wage of those losing their job. Based on administrative data for Germany and two-way fixed effects, we show that worker fixed effects are key for the documented facts. We contrast our empirical results with a search and matching model with worker ex-ante productivity heterogeneity. The simulated model can replicate the empirical facts when calibrated to the measured flow rates and to the relative residual wage dispersion from the administrative data for different wage groups. It is the combination of low steady state separation rates and low residual wage dispersion for high-wage workers that generates the patterns documented in the data.
Keywords: E24; E32; J31; J60; J64; 330; Labor Market Flows; Separations; Fixed Effects; Labor Market Dynamics